Large positive magnetoresistance in semiconducting single-walled carbon nanotubes at room temperature. Issue 19 (13th March 2018) - Nshimiyimana, Jean Pierre; Zhang, Jian; Chi, Xiannian; Hu, Xiao; Wu, Pei; Liu, Siyu; Liu, Jia; Chu, Weiguo; Sun, Lianfeng
Abstract : A positive magnetoresistance is reported in single-walled carbon nanotubes at room temperature, which is further enhanced by etching metallic nanotubes. Abstract : We have investigated the effect of a magnetic field on the resistance (magnetoresistance, MR) of single-walled carbon nanotube (SWNT) arrays. The SWNT devices consist of a mixture of metallic and semiconducting SWNTs between palladium electrodes. The MR of the devices is studied at room temperature and in the presence of perpendicular magnetic fields up to 0.24 tesla. The resistance increases as the external magnetic field becomes higher, suggesting a positive MR of SWNTs. After etching the metallic SWNTs by electrical breakdown, the MR can be further enhanced. Large positive MR values about 15%, 20% and 25% were found in three different devices at 0.24 tesla for semiconducting SWNTs at room temperature. Our results show potential for the development of magneto-electronic devices that are operable at room temperature.